DAYA CERNA (IN VITRO) DAN KARAKTERISTIK PATI BERAS BIRU INSTAN DENGAN PENAMBAHAN EKSTRAK BUNGA TELANG - Puspita Sari; Sih Yuwanti; Dewi Astuti Purnama Sari (Jember University Press, 2020)
Consumption of white rice started to be reduced by diabetics to control the increase in blood glucose. Consumption of rice with IG value and low digestibility can be used as a solution for diabetics. Rice with low digestibility values can be produced by processing rice into instant blue rice using the autoclaving-freezing method and adding telang flower extract as a natural blue coloring and working as an antioxidant. The purpose of this study was to characterize the total levels of starch, amylose, amylopectin, starch digestibility (in vitro) and profile of starch hydrolyzed instant blue rice. The results showed that Membramo and Ciherang 40% instant blue rice had total starch characteristics 73.50% and 74.85%, amylose 22.06% and 25.94%, amylopectin 51.77% and 48.91%, starch digestibility 62.41% and 58.38%. The combination of autoclaving-freezing treatment with added telang flower extracts in both varieties can reduce total starch, amylopectin, and starch digestibility levels and increase amylose content. Decreased digestibility of starch in instant blue rice can reach 17.87% and can produce lower digestibility values compared to Basmati and Taj Mahal rice (comparative rice known as diabetic rice). The hydrolyzed profile of instant blue rice Membramo and Ciherang is lower than blue rice. Hydrolyzed starch profile Membramo instant blue rice is the same as Basmati rice but still cannot reach Taj Mahal rice, while Ciherang instant blue rice reaches Taj Mahal rice and is lower than Basmati rice. Therefore, Membramo and Ciherang instant blue rice has the potential to be an alternative food for diabetics and can also produce innovative food with a low digestibility value Keywords: Instant rice, autoclaving-freezing, telang flower extract